Effects of training exercises for the development of strength and endurance in soccer - Nunez, V. M.; da Silva-Grigoletto, M. E.; Castillo, E. F.; Poblador, M. S.; Lancho, J. L. (The Journal of Strength and Conditioning Research, 2008)
A training program designed to increase strength and aerobic endurance in 1 season was tested on 16 professional soccer players from Spain with a mean age of 28 ± 3.37 years. The schedule comprised 4 macrocycles of 12 weeks of aerobic endurance and strength training. As much for the strength training as for the aerobic endurance, the program used a sequence of general, special, and specific exercises. Assessments were made with routine tests (i.e., squat jumps [SJs], countermovement jumps [CMJs], and countermovement jumps with arm swing [CMJas]) at the end of each macrocycle, and the Probst test was used to assess aerobic endurance as a function of running speed and distance, at the start and end of the training schedule and at the start of the third macrocycle. Jumps were performed on an infrared platform fitted to the MuscleLab system. The Probst test showed differences between the first evaluation and the second and third evaluations: 3,550 ± 411.59 m vs. 2,006 ± 207.20 m (P < 0.01). For 2 of the 3 jumps analyzed, the results were better in the last 2 than in the first 2 evaluations (SJ, 43.13 ± 3.77 vs. 39.47 ± 3.4 [P < 0.05]; CMJ, 49.80 ± 3.77 vs. 46.67 ± 3.76 [P < 0.05]; CMJas, 56.24 ± 5.2 vs. 52.98 ± 4.54 [P > 0.05]). Improvement of aerobic endurance was produced on the first phase of the season as a consequence of the training. To increase strength, it is necessary to augment the number of training sessions of this type. It is convenient to separate aerobic endurance and strength training to create more ample blocks during the last 2 macrocycles.